Investigating the Encouraging Factors for Scholarly Works Contributiontowards Institutional Repository: A Case Study at a Malaysian University - M. R., Abdul Hamid; Noor Azura, Omar; Zainol, Mustafa (2015)
The aim of this paper is to study the encouraging factors for scholarly works contribution towards among academicians at Malaysian university. Methods: This paper uses questionnaire for data collection on the respondents’ perceptional level on the institutional repository efforts in one of the university under study. Several encouraging factors have been identified and to be measured using descriptive statistics. The factors are related to content contribution, i.e. personal factor, professional factor, organizational factor and technological factor. Findings: The study found that all these four encouraging factors did have a relation to the contribution of scholarly works in the university by the academician. Research Limitations: This study used a case study and generalization to all Malaysian universities should be well taken care of. Practical implications: The library at the university should look into these four encouraging factors in order to enhance the contribution from academician towards the repository. Originality/value: This research paper provides basic information for the knowledge management officers in the university by endeavoring more efforts in order to attract more contributions.